EFFECTIVENESS OF USING QUIZLET APLICATION-BASED FLASHCARD MEDIA ON STUDENTS LEARNING OUTCOMES - Khotimah, Khusnul; Kamidjan, Kamidjan; Wiyadi, Heru (IJPSE Indonesian Journal of Primary Science Education, 2020)
The problem that is the focus of the study is the passive learning conditions of students because the teacher explains the material using the old style. The aim of this research was to determine the effectiveness of quizlet aplication-based flashcard media to the thematic learning outcomes of grade IV elementary school students on traditional clothing materials in Indonesia. The research method used pre experimental with one group pretest posttest design. Subject of this research were 32 students in class IV of SDN Kepanjen 1 Jombang school year 2019/2020. Data collection techniques using the test. The data analysis results using the t-test formula. Students are given test before and after learning with quizlet-based flashcard media, from the pretest and posttest conducted, the average results of pretest 50.88 and the average posttest 79.38. Based on the t test results it is known that tcount > ttable or (12.18) > (2.04). Therefore, Ha is accepted while Ho is rejected. Based on the results of the research conducted, it can be concluded that there is effectiveness of used quizlet aplication-based flashcard media learning outcomes of the themes 7 subthemes Beautiful Cultural Diversity of My State Cultureâ€ students of grade IV SDN Kepanjen 1 Jombang in 2020.